Literature Review: Hubungan Stres dan Asupan Gizi terhadap Dismenore Primer pada Remaja Perempuan - Maria Wulandari (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Primary dysmenorrhea is a common reproductive health problem among adolescents and women of reproductive age, significantly affecting quality of life and academic productivity. Psychological stress and dietary patterns are considered important contributing factors influencing the incidence and severity of menstrual pain. This study aimed to analyze the relationship between stress levels and dietary intake with the occurrence of primary dysmenorrhea in adolescents and women of reproductive age. A literature review was conducted using articles published between 2015 and 2025 retrieved from Scopus, PubMed, and Google Scholar. Studies meeting the inclusion criteria were analyzed descriptively and narratively. The findings showed that the prevalence of primary dysmenorrhea ranged from 54.4% to 90.6%. Higher stress levels were significantly associated with increased risk and intensity of menstrual pain (OR up to 4.03). Frequent consumption of sugary foods, fast food, and pro-inflammatory dietary patterns was linked to higher incidence and severity of dysmenorrhea (OR up to 4.8), whereas adequate intake of fruits, vegetables, iron, calcium, and magnesium demonstrated protective effects. Primary dysmenorrhea is multifactorial and significantly associated with stress and dietary intake; therefore, integrated stress management and nutritional education interventions are recommended in adolescent reproductive health programs.